2019
DOI: 10.31413/nativa.v7i6.7984
|View full text |Cite
|
Sign up to set email alerts
|

VARIABILIDADE GENÉTICA UTILIZANDO DESCRITORES MORFOLÓGICOS PARA ACESSOS DE Capsicum spp. PARA FINS ORNAMENTAIS

Abstract: O mercado de pimentas para fins ornamentais é um setor recém explorado, mas com grande potencial de crescimento no ramo de floricultura e paisagismo. As pimenteiras que possuem folhagem variegada, porte baixo, frutos com coloração variada em seus diferentes estádios de maturação, contrastando com as folhagens, já são utilizadas como plantas ornamentais, cultivadas e comercializadas em vasos. O presente trabalho teve como objetivo avaliar a variabilidade genética visando o potencial ornamental de acessos de Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Smaller fruits are, probably, more desirable for ornamental pepper plants, since they show a more harmonious architecture for the plant, creating a better esthetic feature for marketing. According to Luz, Santos & Ambrozio (2019), fruit length, diameter, and weight are affected by the canopy area and width and the higher the canopy measurements, the lower the fruit measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller fruits are, probably, more desirable for ornamental pepper plants, since they show a more harmonious architecture for the plant, creating a better esthetic feature for marketing. According to Luz, Santos & Ambrozio (2019), fruit length, diameter, and weight are affected by the canopy area and width and the higher the canopy measurements, the lower the fruit measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Luz et al (2019) found negative correlations between plant height and fruit length, peduncle length, and fruit weight for Capsicum spp. Roy, Charttejee, Hossain, Basfore & Karak (2018) evaluated C. annuum L. var.…”
mentioning
confidence: 89%